Halo reduction by means of non linear optical elements in the NLC final focus system - Brinkmann, R; Raimondi, P; Seryi, A (2001)
In the Beam Delivery Systems (BDS) for linear colliders that have been designed or built, collimators (or scrapers) are used to suppress backgrounds due to the beam halo. Off-energy and off-axis particles are stopped on the collimator jaws, physically limiting the acceptance of the system. This concept does not scale well to higher beam energy, higher intensity or lower emittance. The increased beam density requires longer and more demanding collimator regions. In contrast, this paper studies the possibility of inserting non-linear optical elements into the Final Focus in order to effectively increase the acceptance of the system. This technique could make the traditional collimation scheme obsolete so that only protection collimators would be needed.